Some biological properties of spiny eel (Mastacembelus mastacembelus, Banks & Solander, 1794) living in the Upper Euphrates River Basin, Turkey - Coban, Mehmet Zulfu; Eroglu, Mucahit; Dusukcan, Mustafa (Nature Portfolio, 2021)
This study was carried out to determine some bioecological characteristics of Mastacembelus mastacembelus, which is the only species of Mastacembelidae family living in Turkey. Fish samples were caught between 2014-2018 from Keban Dam Lake, one of the most important reservoirs of the upper Euphrates Basin. In totally, 348 Mastacembelus mastacembelus individuals were examined, including 178 males and 170 females. The age distributions were defined between the I-XV age groups. Total lengths ranged from 14.20 to 81.80 cm in males and from 15.60 to 77.30 cm in females. Total length-weight relationships were calculated as W=0.0083xTL(2.6516) for males, W=0.0043xTL(2.8310) for females and W=0.0063xTL(2.7256) for all population, and the growth type was estimated as negative allometric. The von Bertalanffy growth parameters for all individuals were computed as L infinity =90.99, k=0.13, t(0)=-0.45. The total (Z), natural (M), fishing (F) mortality rates and exploitation rate (E) were estimated as Z=0.313, M=0.270, F=0.043 and E=0.137, respectively. The length at first capture (Lc) was found as 50.72. The optimum, maximum and economic yields were calculated as E-0.5=0.361; E-max=0.776; E-0.1=0.664, respectively.
Keywords: Solender; Growth